Matemática Financeira: uma meta-análise sob o ponto de vista dos registros de representação semiótica - Schunemann, Tiele Aquino (2016)
This research aims to make a four strict sense investigations synthesis produced by Brazilian instituti-ons that emphasized concepts of financial mathematics developed through educational activities with high school students. Therefore, if adopted as theoretical reference the semiotic representation regis-ters (DUVAL, 2003, 2009, 2011) and the methodological framework meta-analysis (BICUDO, 2014) which can be understood as the realization of a systematic review of a set research intended to culmi-nate in an interpretive synthesis and by analyzing the primary data thereof. The selection of the rese-arch was from a mapping work that highlighted financial mathematics concepts using as source the dissertations relationship and theses published in the Journal Zetetiké, Unicamp, between the years 1993-2011, as well as banks of graduate programs data in the area of Science and Mathematics Educa-tion registered in large multidisciplinary area of the Bank Thesis Coordination Aperfection of Higher Education Personnel - CAPES. It was found that of the 58 studies that emphasized concepts of Finan-cial Mathematics 39 made explicit in its documentary corpus educational activities, among which 08 were developed with high school students. However, it was found that only 04 of these investigations developed, made explicit and included some solutions of students for educational activities that have been proposed. In this context, it was found that the activities the statements were given in the register of natural language and just a matter contemplated the graphic record, while the resolutions of the activities were determined by strategies involving algebraic expressions, the shaft of the arrow and recursion. Such solutions mobilized record in natural language, algebraic / numeric, tabular and cash flow with mostly treatments in cash and numerical flow records.